Influence of Mutagnes on Alcoholic Fermentation by Saccharomyces cerevisiae BR-6 - Singh, S.P.; Pratap, Birendra; Ambastha, B.K.; Kumar Pandey, Ritika; Sinha, A.C.; Prasad, A. (Asian Journal of Chemistry, 2010)
The influence of maleic hydrazide, maganese chloride, hydrazine and 2,4-dinitrophenyl hydrazine were studied on alcoholic fermentation by S. cerevisiae BR-6. It has been found that manganese chloride and hydrazine enhances the production of alcohol while maleic hydrazide and 2,4-dinitrophenyl hydrazine retard the yield.